New torque and flux controllers for direct torque control of induction machines - Toh, C.L; Idris, N.R.N; Yatim, A.H.M (2003)

(untitled)
The new torque and flux controllers with constant switching frequency and low torque and flux ripples for direct torque control induction machine drives are presented. The core of these proposed controllers is based on the comparison between the compensated error signals with high frequency triangular waveforms, thus does not require complex calculation to generate the inverter switching signals. The controllers are therefore can be implemented using analog and/or digital circuits. Modeling and simulation of the new controllers are presented and the results show that the torque and flux ripples are reduced significant